Pengaruh Keberadaan Alun-Alun Sebagai Ruang Publik Terhadap Karakter Kawasan Pusat Kota di Kota Kisaran - Sutresno, Anton; Setioko, Bambang (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2017)
Public space as an element of urban design has an important role in shaping the character of the area. The square has a function as a public space, applying the principles of designing public spaces, as well as having quality as a public space can reflect a strong character of the area. Seeing the importance of the square as the public spaces, than Kisaran City presenting the main square with the provision of facilities and infrastructure. The existence of the town square as a public space in the Kisaran City still not able to accommodate the activities of the user, so there is some use of the square that does not fit its function. In the search field there is still a mix of activities that are within one point as a parking area for vehicles that are also used for gymnastics area, biking, skateboarding, and rollerblading. The lack of facilities in the town square Kisaran shows the low quality of public space that would affect the character of the downtown area. The purpose of this study was to find the effect of the existence of the town square as a public space to the character of the downtown area in the Kisaran city. To know the effect, this study used Rationalistic positivistic paradigm that is based on a quantitative approach with deductive strategies and methods of data collection in the form of literature studies, field surveys, and questionnaires. Methods of data analysis is done through a statistical test by regression using SPSS for evidentiary purposes theory. The results of this study show the effect of the existence of the town square as a public space to the character of the downtown area in the Kisaran city and describes the elements on the square that plays a major role in shaping the character of the downtown area in the Kisaran city.